1996
DOI: 10.1148/radiology.201.2.8888255
|View full text |Cite
|
Sign up to set email alerts
|

Cystic adrenal lesions: CT features.

Abstract: CT findings of a nonenhancing mass with or without wall calcification allow differentiation of adrenal cyst from adenoma. A small adrenal cyst with near-water attenuation and a thin (< or = 3-mm) wall is likely to be benign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 0 publications
0
74
0
10
Order By: Relevance
“…On CT, adrenal cystic lesions are characterized by lack of enhancement with intravenous contrast. The cystic fluid measures water density or higher if hemorrhagic or protein component is presented [46]. On MRI, they are low in signal intensity on T1-weighted images and high on T2-weighted images [23,47].…”
Section: Discussionmentioning
confidence: 99%
“…On CT, adrenal cystic lesions are characterized by lack of enhancement with intravenous contrast. The cystic fluid measures water density or higher if hemorrhagic or protein component is presented [46]. On MRI, they are low in signal intensity on T1-weighted images and high on T2-weighted images [23,47].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previously reported adrenal cysts have been nonfunctioning and asymptomatic [2]. However, a few cases of cystic pheochromocytomas, which are typically solid tumors, have been described [2][3][4][5][6][7][8][9][10]. We describe herein a case of cystic pheochromocytoma that was discovered as an adrenal incidentaloma.…”
Section: Introductionmentioning
confidence: 99%
“…MRI with multiplaner sections would be very helpful for the diagnosis of these complicated cysts, but still there exist some difficult cases which require some invasive examinations. [7] In our case, the cyst itself seems to be an uncomplicated, but the possibility, that its origin is not the right adrenal gland but the right kidney or other retroperitoneal organs, cannot be excluded completely without any invasive studies. Foster classified adrenal cysts into four categories and Tanuma et al recently reported the frequency of each category in Japan (Table 5).…”
Section: Discussionmentioning
confidence: 54%